The impact of IFRS 16 adoption on financial statements of listed South African mining companies - Milan van Wyk; Yolandi Enslin (Cogent Business & Management)
This paper measures the impact of IFRS 16 adoption on financial statements and key financial ratios of mining companies listed on the Johannesburg Stock Exchange (JSE). The IASB has requested research on the adoption of IFRS 16 to understand the impact and assist with post-implementation reviews. Limited studies have been conducted to evaluate the post-implementation impact of IFRS 16. The Wilcoxon signed-rank test was used to determine the impact on financial ratios, and the Kruskal-Wallis test was used to evaluate the impact based on company sizes. The findings illustrated that IFRS 16 increased total assets and liabilities post-adoption. Return-on-asset ratios were not significantly impacted; however, significant changes were noted in debt/equity and debt/asset ratios. Another novel finding is that companies of different sizes were similarly affected by adopting IFRS 16, indicating that the monetary impact of IFRS 16 does not bias based on company size. The research assists users of financial statements to understand the impact of the adoption of IFRS 16 and contributes to the post-implementation review process of the IASB. This article contributes insights into lease capitalisation studies by outlining the impact of IFRS 16’s impact on financial statements and relevant ratios.